Communication Research: Then, Now, and Future - Ni Made Ras Amanda Gelgel (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
This article discusses the state of research in the field of communication science in Indonesia, focusing on the research development themes. Data were gathered via a survey distributed to communication science study programs in Indonesia that are members of the Association for Higher Education Communication Sciences (ASPIKOM). This paper is strengthened by a review of research findings published in various international journals. The data indicates that communication science research in Indonesia has been trending toward technological advancements, primarily focusing on new media and socio-cultural communication. Most research findings are presented at national/international seminars, with the proceedings serving as the final product. Additionally, based on the data, it can be concluded that while communication science continues to develop in Indonesia, it is still not being used as a vehicle for collaborative learning to advance communication science.